Creating an effective learning environment through an E-Learning Instructional Programme (ELIP) - Maria Jakovljevic (Journal of Information and Organizational Sciences, 2009)
Though numerous research reports have provided a body of information about benefits of e-learning there are barriers such as, asynchronous communication channels, lack of personalisation, which decrease the level of interaction between the learner and instructor [13]. The aim of this paper is to discuss and outline a framework on e-learning pedagogical and technology issues which provide a basis for the creation of an e-learning instructional programme (ELIP). The Phase I of this research start with the creation of a framework for an e-learning environment and derivation of the e-learning instructional programme (ELIP); Phase II is aimed to implement a popular audio playback device (iPod) and VoIP. In this phase 40 learners, one instructor and three tutors will be observed and their experiences will be evaluated through focus group interviews and documents analysis. This research was based on a qualitative research approach [78],[44].